The roads we follow [large type] - Deese, Nicole (Deese, Nicole. Fog Harbor romance, 2024)
"A cross-country road trip. A secretive box of journals. An unforgettable summer romance. As the youngest daughter of a country music legend, Raegan Farrow longs to establish an identity away from the spotlight and publish her small-town romances under a pen name. But after her dream is dashed when she won't exploit her mother's fame to further her own career, she hears a rumor from a reliable source regarding a tell-all being written about the Farrow family. Making matters worse, the unknown author has gone to great lengths to remain anonymous until publication. Raegan chooses to keep the tell-all a secret from her scandal-leery sisters as they embark on a two-week cross-country road trip at their mother's request and makes it her mission to expose the identity of the author behind the unsanctioned biography. But all is complicated when she discovers their hired bus driver, Micah Davenport, has a hidden agenda of his own -- one involving both of their mothers and an old box of journals. As they rely on each other to find the answers they seek, the surprising revelations they unearth will lead them down an unexpected road of love and reconciliation."--